PERAN DUKUNGAN SUAMI PADA KEBERHASILAN METODE AMENORE LAKTASI (MAL) DI PUSKESMAS BAYAN KECAMATAN BAYAN KABUPATEN PURWOREJO - Nindya Kurniawati (Jurnal Komunikasi Kesehatan, 2017)
Based on the results of research conducted at the health center Purworejo Bayan Bayan district, there are 52 mothers who had used MAL from 2013 until 2015. The husband support 4 people managed 2 people do not succeed. Type of analytical research, the research design Retrospective study. The sampling technique of total sampling where samples lactation amenorrhea method. When the study March 20 to 12 of April. Results Conclusion:Value chi square statistik is p= 0,001 (p<0,05) with koefisien korelasi 0,406 which means moderate. It can be concluded husband’s relationship data support the success rate in the lactation amenorrhea method Bayan Bayan District Health Center Purworejo Suggestion : Improve data processing by helath centers, especially aboutfamily planning and MCH more cooperative to provide health information to the public about the types of contraception.